2017
DOI: 10.5664/jcsm.6738
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol as a Trigger Affecting Symptom Severity and Frequency of Slow Wave Sleep Disorders

Abstract: Slow wave sleep disorders (SWSD) are unwanted nocturnal behaviors that affect 2% to 5% of adults. 1 The role of alcohol in the pathogenesis of SWSD is controversial, 2 and it has recently been removed as a trigger for these behaviors in the International Classification of Sleep Disorders, Third Edition (ICSD-3). 3 We undertook an audit in our patients with SWSD (n = 126) to examine for association between alcohol and SWSD. A questionnaire reviewing lifestyle factors and triggers that might affect symptom frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It is possible that alcohol could prime abnormal behaviours arising from N3 sleep in predisposed individuals, if precipitating conditions are satisfied. Indeed, 92% of NREM parasomnia patients who consumed alcohol regularly reported that alcohol increased the incidence of their episodes [81] and influenced their sleep quality and symptoms [19,82]. One recent study surveyed the opinions of sleep medicine experts on this issue, and revealed that a clear majority of sleep experts agreed that alcohol could trigger an episode of NREM parasomnias [83].…”
Section: Alcoholmentioning
confidence: 99%
“…It is possible that alcohol could prime abnormal behaviours arising from N3 sleep in predisposed individuals, if precipitating conditions are satisfied. Indeed, 92% of NREM parasomnia patients who consumed alcohol regularly reported that alcohol increased the incidence of their episodes [81] and influenced their sleep quality and symptoms [19,82]. One recent study surveyed the opinions of sleep medicine experts on this issue, and revealed that a clear majority of sleep experts agreed that alcohol could trigger an episode of NREM parasomnias [83].…”
Section: Alcoholmentioning
confidence: 99%